The Antioxidant Activity of Ambon Banana Peel (Musa paradisiaca AAA) against Breast Cancer: A Review - Irwantoho, Graciella Virginia; Immanuel, Joya Angelica; Claire, Ashella Loral Lydia; Sugarda, Aqeela Syakira; Refflyn, Valeska; Lee, Ju Won; Astina, Junaida (Indonesia International Institute for Life Sciences, 2024)
Breast cancer is one of the most prevalent types of cancer in women around the globe, especially those coming from a low-income population like Indonesia. As a preventive measure, consuming balanced diets containing high antioxidant sources are therefore recommended to reduce the risk of breast cancer. Banana peels, for instance, are an undervalued source of antioxidants which also possess high economic and nutritional values. This review aims to provide systematic information about the bioactive composition of ambon banana peels (Musa paradisiaca L. var. sapientum), their antioxidant mechanism on breast cancer, as well as their potential incorporation into food products such as flour, cookies, and chips. The review was conducted by examining literature from the past 10 years (2013-2023) that fit the inclusion criteria. Based on the collected studies, ambon banana peel contains high amounts of bioactive compounds, primarily polyphenols, flavonoids, carotenoids, tannins, saponins, and ferulic acid. Even after the peels are converted into processed food products, the antioxidant activity remains high with proper thermal processing conditions. These antioxidant properties of ambon banana peels provide a promising potential in the treatment of breast cancer through various modes of action, however, clinical studies involving humans are still lacking to further emphasize its therapeutic effects.